2015
DOI: 10.1371/journal.pone.0140077
|View full text |Cite
|
Sign up to set email alerts
|

GATA1 and PU.1 Bind to Ribosomal Protein Genes in Erythroid Cells: Implications for Ribosomopathies

Abstract: The clear connection between ribosome biogenesis dysfunction and specific hematopoiesis-related disorders prompted us to examine the role of critical lineage-specific transcription factors in the transcriptional regulation of ribosomal protein (RP) genes during terminal erythroid differentiation. By applying EMSA and ChIP methodologies in mouse erythroleukemia cells we show that GATA1 and PU.1 bind in vitro and in vivo the proximal promoter region of the RPS19 gene which is frequently mutated in Diamond-Blackf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
6

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 53 publications
0
9
0
6
Order By: Relevance
“…5). Interestingly, a recent study has shown that GATA1 TF binds to the promoter of RPS19 in primary human erythroid cells [54], which in turn has been shown to be essential for the efficient translation of the GATA1 mRNA [29]. Our results thus suggest that key transcriptional regulators orchestrate the production of cell-type-specific transcripts, including those encoding ribosomal proteins.…”
Section: Discussionmentioning
confidence: 60%
“…5). Interestingly, a recent study has shown that GATA1 TF binds to the promoter of RPS19 in primary human erythroid cells [54], which in turn has been shown to be essential for the efficient translation of the GATA1 mRNA [29]. Our results thus suggest that key transcriptional regulators orchestrate the production of cell-type-specific transcripts, including those encoding ribosomal proteins.…”
Section: Discussionmentioning
confidence: 60%
“…Indeed, a recent report showed that GATA1 binds to a subset of ribosome genes, including RPS19 and RPS26 . 45 …”
Section: Resultsmentioning
confidence: 99%
“…In particular, patients demonstrate a notable inability to produce red blood cells with very limited toxicity in other tissues, despite the ubiquitous necessity of ribosomes for all cell types [ 46 ]. Moreover, previous research from our group has shown that ribosome regulation mediated by the cell-fate transcription factors PU.1 and GATA-1 is an integral part of erythroleukemia differentiation [ 47 ]. This ribosome reorganization occurs during the early stages of differentiation (12 h of treatment) and represents a necessary step for erythropoiesis progression [ 47 , 48 ].…”
Section: Discussionmentioning
confidence: 99%